Handbook of Research Methods in Health Social Sciences - Liamputtong, Pranee (Springer Nature Singapore : Imprint: Springer, 2019)
Research is defined by the Australian Research Council as "the creation of new knowledge and/or the use of existing knowledge in a new and creative way so as to generate new concepts, methodologies, inventions and understandings". Research is thus the foundation for knowledge. It produces evidence and informs actions that can provide wider benefit to a society. The knowledge that researchers cultivate from a piece of research can be adopted for social and health programs that can improve the health and well-being of the individuals, their communities and the societies in which they live. As we have witnessed in all corners of the globe, research has become an endeavor that most of us in the health and social sciences cannot avoid. This Handbook is conceived to provide the foundation to readers who wish to embark on a research project in order to form knowledge that they need. The Handbook comprises four main sections: Traditional research methods sciences; Innovative research methods; Doing cross-cultural research; and Sensitive research methodology and approach. This Handbook attests to the diversity and richness of research methods in the health and social sciences. It will benefit many readers, particularly students and researchers who undertake research in health and social science areas. It is also valuable for the training needs of postgraduate students who wish to undertake research in cross-cultural settings, with special groups of people, as it provides essential knowledge not only on the methods of data collection but also salient issues that they need to know if they wish to succeed in their research endeavors.